The Correlation between Critical Thinking and Metacognitive Skills on Student Retention Across Genders in Senior High School - Saleh, Rahmat (2023)
[Objective] The current study explored the correlation and contribution of critical thinking and metacognitive skills toward female and male students' retention in senior high school. [Methodology] This study used a descriptive correlational design, where critical thinking and metacognitive skills served as the predictor, during retention as the criterion. A total of 230 students participated in this study. The participants comprised 112 (48.70%) male students and 118 (51.30%) female students. An essay test and a scoring rubric were used to collect data on participants' critical thinking and metacognitive skills. The research data were analyzed using a multiple regression analysis at a 5% significance level, followed by ANOVA to examine the contribution of critical thinking and metacognitive skills toward male and female students' retention. [Results] The statistical analysis revealed that the simultaneous contribution of critical thinking and metacognitive skills toward female students' retention was higher than that toward male students' retention. The effective contribution values of critical thinking and metacognitive skills toward male students' retention were 2.44% and 10.06%, respectively. Meanwhile, critical thinking and metacognitive skills contributed 7.89% and 12.81% toward female students' retention. [Conclusions] There was a simultaneous correlation between critical thinking, metacognitive skills, and retention of male and female high school students. The effective contribution of critical thinking and metacognitive skills toward female students' retention was more significant than that toward male students' retention. The findings of this study suggest that high school teachers need to consider gender equality when implementing learning strategies to improve critical thinking and metacognitive skills.